2010
DOI: 10.1007/s10695-010-9385-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of enzymatic efficiency on protein digestion in the tilapia Oreochromis niloticus

Abstract: The present study develops an experimental procedure aimed to estimate the efficiency of protein digestion in fish by measuring both gut transit rate and total amount of the main intestinal proteases (trypsin and chymotrypsin). The selected species was the Nile tilapia (Oreochromis niloticus). Total time for digestion, calculated through the estimation of gut transit rate using differently colored feeds, was 7.15 h. Mean production of trypsin and chymotrypsin was 15.94 and 24.11 mU in the proximal intestine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
(44 reference statements)
1
10
0
3
Order By: Relevance
“…Previous studies showed that the peak of trypsin activity in Oreochromis niloticus occurs 6 h after feeding (Uscanga et al., ). In the pepsin enzyme the peak activity in Clarias gariepinus (Uys et al., ), and Cyprinus carpio (Onishi et al., ) was observed 2.5–4 h after and 5 h after feeding, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies showed that the peak of trypsin activity in Oreochromis niloticus occurs 6 h after feeding (Uscanga et al., ). In the pepsin enzyme the peak activity in Clarias gariepinus (Uys et al., ), and Cyprinus carpio (Onishi et al., ) was observed 2.5–4 h after and 5 h after feeding, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…A decrease in the protease-and alkaline phosphatase-specific activities of Rutilus kutum at one hour after feeding in all treatments may be due to dilution by the food and an inadequate secretion rate (Uys et al, 1987). Previous studies showed that the peak of trypsin activity in Oreochromis niloticus occurs 6 h after feeding (Uscanga et al, 2010). In the pepsin enzyme the peak activity in Clarias gariepinus (Uys et al, 1987), and Cyprinus carpio (Onishi Table 5 Changes in specific alkaline phosphatase activity) U mg À1 protein (in Rutilus kutum digestive tract content (mean AE SE, n = 6) after transfer to different salinities in relation to time after feeding et al, 1973) was observed 2.5-4 h after and 5 h after feeding, respectively.…”
mentioning
confidence: 84%
“…In contrast, alkaline proteases exhibit optimum activity at a temperature of 55 °C, which is similar to that found in S. aurata, D. dentex (Alarcón et al, 1998), spotted goatfish Pseudupeneus maculatus (Bloch, 1793) (Souza et al, 2007), parrotfish Sparisoma sp., traira Hoplias malabaricus (Bloch, 1794) (Alencar et al, 2003) and O. niloticus (Bezerra et al, 2005), which show an optimum temperature for alkaline proteases of between 50 and 55 °C, and presents more thermostability, while temperatures from 65 °C only affect 80% of residual activity. However, the activity fall could be compensated by the increasing retention time of food in the digestive tract to perform proteins hydrolysis at lower temperatures than optimal (Alarcón et al, 1998;Uscanga et al, 2010). It should be mentioned that optimal temperature values and thermal stability of protease activities are only operational parameters of the enzymes, rather than results of physiological importance; which can be associated with the configuration of enzymes as well as the habitat, environment and genetic aspects of the species (Nalinanon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the temperature optima and the thermal stability of the digestive proteases are only operational parameters of enzymes, rather than physiologically relevant results, since activities may vary with enzyme configuration, habitat, environment and genetic aspects of the species [30,32,38]. This deficiency in activity is compensated, however, by a longer retention of food in the digestive system to perform the hydrolysis of proteins at lower temperatures than optimal [10,32,39,41]. Determination of the number of isoforms that constitute acid proteases in C. beani was performed using the specific inhibitor pepstatin A, which inhibited the activity of acidic proteases by 86%.…”
Section: Discussionmentioning
confidence: 99%